Photoperiod Affects Harderian Gland Morphology and Secretion in Female Cricetulus barabensis: Autophagy, Apoptosis, and Mitochondria - Wang, Zhe; Xu, Jin-Hui; Mou, Jun-Jie; Kong, Xiao-Tong; Wu, Ming; Xue, Hui-Liang; Xu, Lai-Xiang (Frontiers in Physiology, 2020)
Photoperiod is an important factor of mammalian seasonal rhythm. The Harderian gland (HG) appears to act as a “standby” structure of the retinal-pineal axis, mediating light signals in vitro and neuroendocrine regulation in vivo; however, the effect of photoperiod on the HG is not clear. Here, we studied morphological differences in the HG of female striped dwarf hamsters (Cricetulus barabensis), a small mammal that experiences an annual rhythm, under different photoperiods (i.e., short photoperiod, SP; moderate photoperiod, MP; long photoperiod, LP), and further investigated the molecular mechanisms related to these morphological differences. Results showed that body weight, carcass weight, and HG weight were higher in the SP and LP groups than that in the MP group. Protein expression of hydroxyindole-o-methyltransferase, a key enzyme in melatonin synthesis, was higher in the SP group than in the other two groups. Somatostatin showed highest expression in the LP group. Furthermore, comparison of changes in the HG ultrastructure demonstrated autolysosome formation in the SP group. Protein aggregation and mRNA expression of LC3 and protein expression of LC3II/LC3I were higher in the SP group than in the MP group, indicating elevated autophagy under SP. Chromatin agglutination and mitochondrial damage were observed and bax/bcl2 and cytochrome C expression increased at the protein and mRNA levels in the SP and LP groups, suggesting increased apoptosis. Protein expression of dynamin-related protein 1 and mitochondrial fission factor (Mff) were highest in the SP group, suggesting elevated mitochondrial fission. Protein expression levels of adenosine triphosphate (ATP) synthase and citrate synthase were lower in the LP group than in the SP and MP groups. These results indicated that autophagy and apoptosis imbalance under SP and LP conditions may have led to HG weight loss and up-regulation of mitochondrial apoptosis may have weakened mitochondrial function under LP conditions. Finally, melatonin synthesis appeared to be positively correlated with the time hamsters entered darkness.